Real-Life Indications of Interleukin-1 Blocking Agents in Hereditary Recurrent Fevers: Data From the JIRcohort and a Literature Review - Vinit, Caroline; Georgin-Lavialle, Sophie; Theodoropoulou, Aikaterini; Barbier, Catherine; Belot, Alexandre; Mejbri, Manel; Pillet, Pascal; Pachlopnik, Jana; Poignant, Sylvaine; Rebelle, Charlotte; Woerner, Andreas; Koné-Paut, Isabelle; et al. (Frontiers in Immunology, 2021)
Background: Interleukin (IL)-1 inhibitors represent the main treatment in patients with colchicine resistant/intolerant familial Mediterranean fever crFMF), mevalonate kinase deficiency (MKD) and periodic tumor necrosis factor receptor-related syndrome (TRAPS). However, the reasons for the use of IL-1 inhibitors in these diseases are still not completely clarified. Objective: Identify real life situations that led to use anakinra or canakinumab treatment in hereditary recurrent fevers (HRF), combining data from an international registry and an up-to-date literature review. Patients and Methods: Data were extracted from the JIRcohort, in which clinical information (demographic data, treatment, disease activity and quality of life) on patients with FMF, MKD and TRAPS were retrospectively collected. A literature search was conducted using Medline, EMBASE and Cochrane databases. Results: Complete data of 93 patients with HRF (53.8% FMF, 31.2% MKD and 15.1% TRAPS) were analyzed. Data from both the registry and the literature review confirmed that the main reasons for use of IL-1 blockers were: failure of previous treatment (n=57, 61.3% and n=964, 75.3% respectively), persistence of disease activity with frequent attacks (n=44, 47.3% and n=1,023, 79.9%) and/or uncontrolled inflammatory syndrome (n=46, 49.5% and n=398, 31.1%), severe disease complication or associated comorbidities (n=38, 40.9% and n=390, 30.4%), and worsening in patients' quality of life (n=36, 38.7% and n=100, 7,8%). No reasons were specified for 12 (16.4%) JIRcohort patients and 154 (12%) patients in the literature. Conclusion: In the absence of standardized indications for IL-1 inhibitors in crFMF, MKD and TRAPS, these results could serve as a basis for developing a treat-to-target strategy that would help clinicians to codify the therapeutic escalation with IL-1 inhibitors.